Penerapan Model Project Based Learning dalam Pembelajaran Bahasa Indonesia di SMP Negeri 1 Pallangga Kabupaten Gowa - Rahmi, Nur; Jahrir, Andi Sahtiani; Saleh, Muhammad (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to describe the planning, implementation, and students' perceptions of the implementation of the Project Based Learning (PjBL) model in Indonesian language learning at SMP Negeri 1 Pallangga, Gowa Regency. This study used a qualitative approach with a case study design. Data were obtained through observation, interviews, and documentation involving three Indonesian language teachers and 15 students in grades VII and VIII. Data analysis used the interactive model of Miles and Huberman which includes data reduction, data presentation, and drawing conclusions. The results showed that teachers designed project-based activities by referring to learning objectives, activity steps, media selection, and assessment rubrics. The implementation of learning followed the six main syntaxes of Project Based Learning (PjBL), although the reflection stage was not optimal due to time constraints. Student responses were generally positive, namely 13 out of 15 students stated that Project Based Learning (PjBL) increased their creativity, engagement, collaboration, and understanding. Challenges faced included time management and uneven group participation. Thus, the Project Based Learning (PjBL) model has the potential to improve the quality of Indonesian language learning through meaningful and contextual tasks.